Salah al-Din al-Ayyubi’s policy towards the Crusaders after the liberation of Jerusalem - Al-Mahasneh, Hadi Abdel-Fattah; Busaidi, Ibrahim bin Yahya Al; Al-Tarawneh, Mohamed Salem (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to show the policy in which Sultan Salahuddin Al-Ayyubi and Muslims treated the Crusader groups present in the city of Jerusalem after liberating them from the Crusader occupation after they ruled them for more than ninety years. Salah al-Din tolerated them and secured them for their lives and properties, and compared that to the treatment that the Crusaders followed towards the people of The holy city when it was occupied in the year 492 AH / 1098 CE. It is clear from this study that Sultan Salahuddin Al-Ayyubi treated the Crusaders in a good way and treated them well, so he secured their lives and preserved their money and possessions, and no one was allowed to attack them and ordered that they be protected until they reached their safe place in Tire where the Crusaders were gathering there after their defeat in the battle of Hattin and Tahrir. Holy city. Salah al-Din did not follow the approach of the Crusaders, who brought down the people of safe Jerusalem, the classes of killing and torture, and destroyed the holy sites and plundered what was in them and turned them into stables for them and their horses until God swapped them with Sultan Salahuddin and he freed them. This study aims to show the policy in which Sultan Salahuddin Al-Ayyubi and Muslims treated the Crusader groups present in the city of Jerusalem after liberating them from the Crusader occupation after they ruled them for more than ninety years. Salah al-Din tolerated them and secured them for their lives and properties, and compared that to the treatment that the Crusaders followed towards the people of The holy city when it was occupied in the year 492 AH / 1098 CE. It is clear from this study that Sultan Salahuddin Al-Ayyubi treated the Crusaders in a good way and treated them well, so he secured their lives and preserved their money and possessions, and no one was allowed to attack them and ordered that they be protected until they reached their safe place in Tire where the Crusaders were gathering there after their defeat in the battle of Hattin and Tahrir. Holy city. Salah al-Din did not follow the approach of the Crusaders, who brought down the people of safe Jerusalem, the classes of killing and torture, and destroyed the holy sites and plundered what was in them and turned them into stables for them and their horses until God swapped them with Sultan Salahuddin and he liberated them.